2006
DOI: 10.1007/s00277-005-0044-6
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin plus granulocyte colony-stimulating factor is better than erythropoietin alone to treat anemia in low-risk myelodysplastic syndromes: results from a randomized single-centre study

Abstract: Haemopoietic growth factors (HGF), i.e. erythropoietin [recombinant human erythropoietin (rHEPO)] or granulocyte colony stimulating factor (G-CSF), alone or in combination, have largely been used to treat anemia in myelodysplastic syndromes (MDS), but whether combined rHEPO and G-CSF is really superior to rHEPO alone is still under debate. In particular, randomized studies comparing front-line rHEPO vs rHEPO+G-CSF are still lacking. The aim of this study was to compare the effects of "standard" doses of rHEPO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 27 publications
3
55
0
1
Order By: Relevance
“…28 In patients resistant to an ESA alone, its combination with G-CSF or GM-CSF also yields 20-40% erythroid responses. 6,[29][30][31][32][33] However, ESA-G-CSF combinations give disappointing results in patients with high endogenous EPO levels, 7 similar to what we observed with the epoetin-b-ATRA combination.…”
Section: Side Effects Of Epoetin-b-atra Combinationsupporting
confidence: 59%
“…28 In patients resistant to an ESA alone, its combination with G-CSF or GM-CSF also yields 20-40% erythroid responses. 6,[29][30][31][32][33] However, ESA-G-CSF combinations give disappointing results in patients with high endogenous EPO levels, 7 similar to what we observed with the epoetin-b-ATRA combination.…”
Section: Side Effects Of Epoetin-b-atra Combinationsupporting
confidence: 59%
“…Several studies have reported a positive correlation between Hb levels and HRQoL [9,19,20,[24][25][26][27][28][29][30][31], although this correlation is not consistent [6]. The current data reinforce the notion of a relationship between Hb levels and QOL-E© as specific patient-reported outcome in MDS patients.…”
Section: Discussionsupporting
confidence: 76%
“…However, because of the cost, only 1 of our patients who could afford some doses of rhEpo had the growth factor, which was however not found to be effective. Studies have however shown that best results are obtained when rhEpo is combined with G-CSF (14). Although only one patient presented with marked leucopenia, and three with significant neutropenia (Tables 1 and 2), more than 50% of them presented with features of infection at presentation.…”
Section: Discussionmentioning
confidence: 98%